Bacillus altitudinis MT422188: a potential agent for zinc bioremediation. Issue 3 (3rd July 2022) - Khan, Maryam; Ijaz, Munazza; Chotana, Ghayoor Abbas; Murtaza, Ghulam; Malik, Arif; Shamim, Saba
Abstract: Anthropogenic processes are one of the main contributors for the presence of heavy metals in air, land and water sources, leading to environmental pollution. In the present study, Bacillus altitudinis MT422188 was used for determining its potential role in zinc bioremediation. After the bacterium was isolated and characterized, its optimum growth conditions were determined. The growth parameters, antioxidative and biosorption potential, motility and chemotactic behavior, as well as physicochemical nature of the isolate was determined in the presence and absence of zinc. Optimum growth was observed at pH 7, 37 °C and at 1 mM phosphate. Minimum inhibitory concentration was found to be 20 mM for Zn 2+ whereas metal resistance pattern for other heavy metal ions was Cu 2+ (30 mM) > Ni 2+ (25 mM) > Cr 6+ (18 mM) > Pb 2+ (12 mM) > Co 2+ (8 mM) > Cd 2+ (5 mM) > Hg 2+ (3 mM). EC50 was found to be 3.4 mM Zn 2+ . Biosorption experiments in the presence of metal, DCCD and DNP in both live and killed cells demonstrated metal uptake, intracellular Zn 2+ accumulation and adsorption by ATP independent efflux system. It was also found to effectively remove 81 mg/L and 87 mg/L after a period of 4 and 8 days, respectively. In the presence of Zn 2+, positive chemotaxis was demonstrated where Zn 2+ acted as a chemoattractant. Zn 2+ induced elevated levels of GR, SOD and POX, while APOX and CAT activity were inhibited by it. The appearance of 92 kDa protein band in B. altitudinis under Zn 2+ stress confirmed the induction of metallothionein. FTIR analysis revealed the active role of amide, hydroxyl, and carboxyl groups in combating Zn 2+ stress. SEM and EDS analysis revealed surface adsorption of Zn 2+ ions by bacterial cells. The experimental data obeyed the Freundlich isotherm model and pseudo second-order kinetics, indicating it to be an efficient biosorbent for Zn 2+ . This study revealed the potential application of B. altitudinis MT422188 in the bioremediation of Zn 2+ from polluted wastewaters.